Child Anxiety Profiles in Chilean Elementary School Students and Academic Self-Attributions in Mathematics - Aitana Fernández-Sogorb (SAGE Publishing, 2021)
The present study had a dual objective: to verify the existence of profiles of anxious students and to relate the possible profiles with causal self-attributions in the area of mathematics. The sample consisted of 1,730 Chilean children from 9 to 11 years old ( M  = 10.05; SD =  1.03). The Visual Analog Scale for Anxiety-Revised and the Sydney Attribution Scale were administered. Four profiles were found by using the latent class analysis: Low Anxiety , Moderate Anxiety , Moderate Anxiety School-type and High Anxiety . The High Anxiety profile tended to attribute its failures more to ability and effort. However, the Moderate Anxiety School-type group showed a greater tendency to attribute its failures to external causes and its successes to effort. The practical implications of these findings for improving the attributional style and the anxiety levels of each profile are discussed.